2013
DOI: 10.1038/ki.2013.136
|View full text |Cite
|
Sign up to set email alerts
|

A history of chronic opioid usage prior to kidney transplantation may be associated with increased mortality risk

Abstract: Chronic opioid usage (COU) for analgesia is common among patients with end-stage renal disease. In order to test whether a prior history of COU negatively affects post-kidney transplant outcomes, we retrospectively examined clinical outcomes in adult kidney transplant patients. Among 1064 adult kidney transplant patients, 452 (42.5%) reported the presence of various body pains and 108 (10.2%) reported a prior history of COU. While the overall death or kidney graft loss was not statistically different between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…: kidney transplant recipients’ self-reported long-term opioid use before transplant was associated with a 2-fold higher risk of death but similar risk of graft loss; graft loss risk was not based on self-reported medication use but identified through chart review. (18) The kidney transplant evaluation period is an opportunity for the transplant team to review the candidate’s comorbid conditions and medication list to assess risks, and counsel and optimize care before surgery. Pretransplant opioid use may become more prevalent, since end-stage renal disease (ESRD) patients have multiple potential sources of acute and chronic pain, including underlying causes of ESRD (e.g., polycystic kidney disease), other comorbidity (e.g., diabetes mellitus), renal complications (e.g., calciphylaxis), and vascular access complications (e.g., steal syndrome with arteriovenous fistulas).…”
Section: Discussionmentioning
confidence: 99%
“…: kidney transplant recipients’ self-reported long-term opioid use before transplant was associated with a 2-fold higher risk of death but similar risk of graft loss; graft loss risk was not based on self-reported medication use but identified through chart review. (18) The kidney transplant evaluation period is an opportunity for the transplant team to review the candidate’s comorbid conditions and medication list to assess risks, and counsel and optimize care before surgery. Pretransplant opioid use may become more prevalent, since end-stage renal disease (ESRD) patients have multiple potential sources of acute and chronic pain, including underlying causes of ESRD (e.g., polycystic kidney disease), other comorbidity (e.g., diabetes mellitus), renal complications (e.g., calciphylaxis), and vascular access complications (e.g., steal syndrome with arteriovenous fistulas).…”
Section: Discussionmentioning
confidence: 99%
“…A single center study recently found associations of pre-transplant opioid use identified from chart review with post-transplant death [13], while we recently found associations of pre-transplant narcotic use defined by pharmacy fill records with increased risks of post-transplant death and graft loss in a larger national sample [14]. In the current study, we expanded our linkage of national transplant registry data and outpatient pharmacy fill records to incorporate Medicare billing claims as measures of clinical conditions diagnosed after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Barrantes et al . performed a retrospective single-center study of 1064 kidney transplant recipients followed for a median of 48 months (interquartile range [IQR], 34 to 63), and found that 452 recipients (42%) had a history of chronic pain prior to transplantation and 108 (10%) reported chronic opioid use prior to transplantation [13]. In the adjusted analyses, recipients with a history of chronic opioid use had a 2-fold higher risk of death, but similar risk of graft loss compared to matched recipients without a history of chronic opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…Cocaine and opioid abuse are usually absolute contraindications; tobacco and alcohol use or abuse are often relatively contraindicated. The use of these substances has been linked to graft loss, delayed graft function, and patient mortality . Any MJ use, on the other hand, is frequently banned as an absolute contraindication.…”
Section: Introductionmentioning
confidence: 99%